2011
DOI: 10.1002/app.35508
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar arrangements of linear polyethylene in ultrathin films

Abstract: The crystal orientations of linear polyethylene films on silicon substrates are investigated using grazing incidence X-ray diffraction and atomic force microscopy. From diffraction analysis, we can identify the structural arrangement of PE crystals in ultrathin film. The orientation of lamellar crystal in PE films changes from edge-on to flat-on with the decrease of film thickness in the film thickness below $ 100 nm. The slightly inclined lamellae relative to the substrate are found to coexist with the flat-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…These results indicated that, after being annealed at 135 °C for 10 min and recrystallized by cooling to room temperature, the a -axis of PE in leaf-shaped crystals was preferentially oriented in two different directions at azimuthal angles ≈44° and ≈56° from the substrate plane. These results showed that the crystal orientation was similar with the structural arrangement of PE crystals in ultrathin films (with a thickness of about 52 nm) obtained by spin-coating . Considering the morphology revealed by AFM in Figure , we tentatively conclude that after recrystallization, both a - and c -axes of most crystals were tilted, resulting in slightly inclined terrace-like lamellae.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…These results indicated that, after being annealed at 135 °C for 10 min and recrystallized by cooling to room temperature, the a -axis of PE in leaf-shaped crystals was preferentially oriented in two different directions at azimuthal angles ≈44° and ≈56° from the substrate plane. These results showed that the crystal orientation was similar with the structural arrangement of PE crystals in ultrathin films (with a thickness of about 52 nm) obtained by spin-coating . Considering the morphology revealed by AFM in Figure , we tentatively conclude that after recrystallization, both a - and c -axes of most crystals were tilted, resulting in slightly inclined terrace-like lamellae.…”
Section: Resultssupporting
confidence: 73%
“…From the magnified images (Figure c,d), it became evident that these regions consisted of lamellae of different orientations, labeled by letters E and F. Region E was composed of lamellae in the edge-on orientation, whereas region F consisted of twisted and orderly stacked lamellae, most of them lying flat-on. This morphology reminds us of lamellar twisting, a common phenomenon for PE and other polymers. Lamellar twisting has been established in banded spherulites, where the band spacing depends on crystallization temperature. In the present case, the band period was not constant but varied in different regions.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…For the film with the thickness approaching the radius of gyration of polymer M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 chains, flat-on lamellae are usually observed. This film thickness dependence of lamellar orientation is widely encountered in many polymer systems [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. For example, Schönherret et al have found that for poly(ethylene oxide) thin films on the oxidized silicon substrate lamellae are oriented edge-on when the films are thicker than 1 µm, while in the films thinner than 300 nm lamellae are preferentially flat-on [9].…”
Section: Introductionmentioning
confidence: 97%
“…[24] The thickness of PE films without and with porous structures reached down to 28 and 100 nm, with limited lateral size and absolute mechanical strength. [25,26] Towards a high aspect ratio, scalable PE microporous membranes driven by the application as lithium-ion battery separators have been intensively investigated., e.g., meter-square size of UHMWPE nanofibrous membranes with micrometer-level thickness, [27] and large-area UHMWPE membranes of 12-micrometer-thick used as radiative cooling fabric and electrocatalytic interface have been prepared. [28,29] Despite their outstanding properties and diverse applications, the simultaneous realization of low dimensionality down to lamellar thickness and large lateral size up to square-meter level is still to be accomplished.…”
Section: Introductionmentioning
confidence: 99%